The Ressurection of the Tremas Islamic Boarding School After the Fatrah Era (1948-1965): A Consequence of the Madiun PKI Revolt in 1948 - Roro Wilis; Wildhan Ichzha Maulana (Criksetra: Jurnal Pendidikan Sejarah, 2026)
This study examines the sustainability of Tremas Islamic Boarding School following the fatrah period (1948–1965), triggered by the 1948 Madiun PKI rebellion, while also highlighting its revival during the fatrah period (1948–1952). Using a historical approach involving heuristics, source criticism, interpretation, and historiography, data were obtained from oral accounts of Kyai Hamid Dimyathi’s descendants and relevant literature. The findings reveal that the sustainability of Tremas Islamic Boarding School was not determined by a single leadership model but by collective leadership established through family deliberation. During the fatrah period, educational activities continued on a limited basis through traditional learning systems. From 1952 onward, the pesantren’s revival was supported by three complementary forms of social capital: genealogical social capital within the leaders’ family, social capital based on networks of ulama and alumni across pesantren, and regional santri organizational social capital, which expanded networks of religious outreach and alumni. These forms of social capital provided the foundation for physical rehabilitation and spatial reorganization, curriculum renewal, the development of students’ talents and interests, region-based student organizations, and institutional management based on the division of leadership roles. The findings contribute to scholarship on pesantren resilience by demonstrating that the sustainability of Islamic educational institutions during periods of crisis depends not only on leadership continuity but also on the ability to mobilize social networks and develop adaptive institutional governance.